OCT-NIRS Imaging for Detection of Coronary Plaque Structure and Vulnerability - Muller, James; Madder, Ryan (Frontiers in Cardiovascular Medicine, 2020)
This is a review article. I am not sure an abstract is needed. If so one can be done.